Characteristics and Diversity of Riparian Plant Species in Relation to Plastic Litter Entrapment in the Bedog River, Indonesia - Utami, Inggita; Tanaka, Nobuaki (Journal of Biotechnology and Natural Science, 2025)
The increasing production of waste and inadequate waste management on land have led to significant plastic leakage into river systems. Riparian vegetation is now increasingly covered by plastic debris, posing a threat to essential biological processes such as pollination and plant metabolism. The aim of this study is to identify the characteristics and types of riparian plant species that trap plastic litter along the riparian zones. The research was conducted in Indonesia, specifically in Yogyakarta Province, which is currently facing a waste management crisis. Bedog River was selected as the sampling site due to its course through densely populated areas, including Sleman and Bantul Regencies. A total of 20 sampling plots, spaced one to two kilometers apart, were distributed along the river, with each plot containing a 25-square-meter sampling plot designated for plant identification. In total, 78 plant species, predominantly from the Poaceae, Moraceae, and Fabaceae families, were found to trap plastic debris. Branches and twigs were the most frequently affected plant structures. Bamboo and shrubs exhibited distinctive morphological characteristics that facilitated plastic entrapment, particularly of small plastic fragments. A substantial portion of riparian vegetation along the Bedog River is covered with plastic waste, necessitating targeted conservation efforts for affected species.